Regional cerebral blood flow changes after bilateral external carotid artery ligation in acute experimental infarction. - Abraham, J (1975)
Regional cerebral blood flow (rCBF) was measured in baboons by intracarotid injection of 133Xe and a gamma camera after acute cerebral infarction was induced by occlusion of the middle cerebral artery (MCA). A steady state of rCBF was measured four hour after MCA occlusion and was followed by bilateral ligation of the external cartoid arteries (ECA). Subsequent rCBF measurements were obtained at 30, 60, and 120 minutes. After bilateral ECA ligation, flow in ischaemic and non-ischaemic areas was greatly enhanced and flow in the hyperaemic areas significantly reduced, presumably since they had provided collateral circulation to the ischaemic zone with a favourable redistribution.